An EST approach to entrepreneurial exit in Chinese family business: A case study of H company - ZHANG, Lidian (Institutional Knowledge at Singapore Management University, 2022)
Previous entrepreneurial exit literature has mostly followed a feature-oriented logic by summarizing the impact of industry and company characteristics and entrepreneurs’ personal traits on entrepreneurial exit decisions, disregarding the decision-making process of entrepreneurial exit and the role of key events in advancing the process. This thesis endeavors to explore the determining factors behind entrepreneurial exit decisions of family businesses and the dynamic decision-making process based on Event System Theory (EST) with a single-case study method and a feature-oriented and process-oriented approach. This study has conducted an in-depth investigation into Company H, which possesses typical features of Chinese private family businesses. The findings are as follows: (1) Both exogenous and endogenous events affect entrepreneurial exit decisions through unfulfilled family expectations (family wealth expectation, family reputation expectation, family harmony expectation, and family succession expectation); (2) Industry characteristics (industry competition intensity, government regulation intensity and negative media coverage intensity) not only can affect entrepreneurial exit directly but may also act as moderating factors that mediate the impact of key events on entrepreneurial exit; and (3) Family characteristics (family wealth accumulation, degree of ownership concentration and degree of the next generation’s involvement) not only have a direct impact on entrepreneurial exit but may also exert moderating effects on the process from key events to family expectations to entrepreneurial exit. In addition, the study has also collected publicly available information from another private company that has experienced the same events during the same period in the industry and carried out a supplementary analysis based on the framework and methodology of EST to support the findings of the case study further. The possible contributions of this study are as follows: (1) It contributes to the previous research on entrepreneurial exit by providing an in-depth analysis of how family businesses make entrepreneurial exit decisions in terms of event strength and event space with a new perspective of EST; (2) It examines entrepreneurial exit in the context of Chinese family businesses and focuses on how key events affect entrepreneurial exit through family expectations, which helps to shed light on the mechanism through which key events exert influence on founders’ entrepreneurial exit decisions; and (3) It has integrated the process-oriented and feature-oriented paradigms by including industry characteristics and family characteristics as important situational conditions, thus setting boundary conditions for the process by which key events affect entrepreneurial exit. The practical implications of these findings are discussed.